BILE ACIDS AS SPECIFIC FAECAL POLLUTION INDICATORS IN WATER AND SEDIMENTS - Obuseng, Veronica C.; Moshoeshoe, Mohau; Nareetsile, Florence (European Scientific Journal, ESJ, 2013)
Microbiological indicators such as Escherichia coli (E. coli) have been extensively applied to monitor sewage contamination in waters and sediments. However, it has been accomplished by many researchers that microorganism indicators of faecal pollution in aquatic environments have limited applicability, owing to their lack of specificity and variable life span induced by environmental factors such as sunlight and chlorination. This review highlights the use of chemical indicators for faecal or sewage pollution monitoring. It highlights that the differences in bile acid distributions in animal faeces could be utilized to differentiate inputs in an environment. Furthermore, the high resistance to degradation by some of the bile acids would make them better suited for long standing pollution compared to coprostanol, as it is more readily degraded. Bile acid data could be used in conjunction with other available evidence, be it ethnographic or as part of a multi-biomarker approach, employing 5-stanols and bacterial indicators, such as C. perfringens, to distinguish amongst the different environmental inputs.